Opportunistic Scheduling in IRS-Aided UAV Multi-User Wireless Communication Systems: Modeling and Analysis - Neha Choudhary; Sandeep Joshi; Vinod Kumar Chaubey (IEEE Access)
In this paper, we present the performance analysis of an opportunistic scheduling-based intelligent reflecting surface (IRS)-aided unmanned aerial vehicle (UAV) multi-user wireless communication system. We consider an IRS mounted on a UAV and the communication links between transmitter and receiver to be Rician faded. The considered IRS-aided UAV communication system performs opportunistic scheduling for user selection and transmission, assuming the practical limitation of outdated channel state information (CSI). We provide an analytical framework for the IRS-aided UAV wireless communication system and derive expressions for outage probability, asymptotic outage probability, ergodic capacity, effective capacity, and symbol error rate (SER) considering M-ary phase shift keying modulation. We show the performance variations with the CSI parameter, the number of reflecting elements, the Rician factor, and the delay constraint. We observe that a lower delay constraint value results in higher effective capacity. Furthermore, the analytical results are verified through system simulations.